98.0k views
4 votes
3(4x + 1) – 4x + 3 = -18

2 Answers

2 votes

Answer:

x= -3

Explanation:

SOOOOO, we're going to distribute, okay?

3(4x+1) = 12x+3

so now

12x+3-4x+3= -18

SO now we combine like terms, okay?

8x+6= -18

-6 -6

8x= -24

x= -3

User Wasif Kirmani
by
5.4k points
3 votes

Answer:


x=-3

Explanation:


3(4x + 1) - 4x + 3 = -18

Subtract 3 from both sides:


3\left(4x+1\right)-4x+3-3=-18-3


3\left(4x+1\right)-4x=-21

Expand:


3*4x+3* 1-4x=-21


12x+3-4x=-21


8x+3=-21

Subtract 3 from both sides:


8x+3-3=-21-3


8x=-24

Divide both sides by 8:


(8x)/(8)=(-24)/(8)


x=-3

User Thilaga
by
4.8k points